Diffusion-Weighted Magnetic Resonance Imaging Findings of Kidneys with Obstructive Uropathy: Differentiation between Benign and Malignant Etiology - Tugce Ozlem Kalayci; Melda Apaydin; Fitnet Sönmezgöz; Sinan Çalık; Melike Bedel Koruyucu (The Scientific World Journal)
Purpose. In this study, we aimed to evaluate the capability of diffusion-weighted magnetic resonance imaging (DWI) in differentiation between benign and malignant etiology of obstructive uropathy. Materials and Methods. DWI was performed in 41 patients with hydronephrotic kidneys and 26 healthy volunteers. MR imaging was performed using a 1.5 T whole-body superconducting MR scanner. The signal intensities of the renal parenchyma on DWI and apparent diffusion coefficient (ADC) maps were noted. DWI was performed with the following diffusion gradient b values: 100, 600, and 1000 s/mm2. A large circular region of interest was placed in the corticomedullary junction of the kidneys. For statistical analysis, the independent-samples t test was used. Results. The mean renal ADC values for b100, b600, and b1000 in hydronephrosis patients with benign and malignant etiology and the healthy volunteers of the control group were analysed. ADC measurements of renal parenchyma in all hydronephrotic kidneys with benign and malignant etiology were found to be statistically low compared to those of normal kidneys P<0.05. Conclusions. There were significant differences in the ADC values of obstructed kidneys compared to those of normal kidneys. Obstructed kidneys with malignant etiology had lower ADC values for b1000 compared to obstructed kidneys with benign etiology, but these alterations were statistically insignificant.